2018
DOI: 10.19102/icrm.2018.090303
|View full text |Cite
|
Sign up to set email alerts
|

Amiodarone-induced Hyponatremia: A Case Report and a Review of the Literature

Abstract: Amiodarone is a widely used medication for controlling various types of cardiac arrhythmias. Nonetheless, it carries several known adverse effects that may preclude its use or necessitate discontinuation. Hyponatremia resulting from amiodarone is rarely reported, and its incidence is unknown. We present a case of severe hyponatremia secondary to amiodarone therapy and a review of the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The authors also highlighted the possibility that this adverse effect may be due to a prerequisite genetic predisposition or polymorphism given the rarity of its occurrence and suggested further research is necessary to explore the potential mechanisms and drug targets that could lead to hyponatremia. 9…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors also highlighted the possibility that this adverse effect may be due to a prerequisite genetic predisposition or polymorphism given the rarity of its occurrence and suggested further research is necessary to explore the potential mechanisms and drug targets that could lead to hyponatremia. 9…”
Section: Discussionmentioning
confidence: 99%
“…The majority of reported cases were seen among elderly male patients, and most patients had comorbid conditions such as hypertension, hyperlipidemia, congestive heart failure, and arrhythmia, with the duration of amiodarone therapy ranging from less than 24 hours to 5 years before the development of hyponatremia. [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] The adverse effects reported in these cases include altered mental status, torsades de pointes, dizziness, hypotension, generalized weakness, and loss of appetite. Adrenal insufficiency and thyroid dysfunction was ruled out in all the reported cases.…”
Section: Discussionmentioning
confidence: 99%
“…4 Amiodarone-induced hyponatremia is a rare complication, with only 17 cases described in the literature. 26 The first case report was published in 1996. 27 The mechanism by which amiodarone induces SIADH is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Rhythm Management, Barham et al, in the format of a case report and a review of the literature, 4 call attention to an infrequently reported adverse consequence of amiodarone use that I strongly suspect is not known to most practitioners or clinical pharmacologists; that is, marked hyponatremia, which most likely occurred due to the inducement of the syndrome of inappropriate secretion of antidiuretic hormone (SIADH). Their report details the time course as related to amiodarone use, both with respect to its appearance and its termination.…”
Section: In This Issue Of the Journal Of Innovations In Cardiacmentioning
confidence: 99%